2009
DOI: 10.1007/s11695-009-9860-4
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Empyema After Laparoscopic Adjustable Gastric Banding. A Rare Complication

Abstract: The laparoscopic adjustable gastric banding (LAGB) is a popular therapeutic option for morbid obesity. It is a minimally invasive procedure. The reported early morbidity is low and there are only few reports of respiratory complications. We report a case of empyema and lung abscess due to diaphragm perforation by a LAGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Two patients were reported by Alamoudi 10 one with AP and the other case of pneumonia due to migration of a connecting catheter. A case of thoracic empyema was reported by Krassas et al 11 A case of recurrent AP after LAGB was reported by Hofer et al 12 Zimlichman et al 13 reported a case of lung abscess. Nemni 14 reported a case of severe chronic cough after LAGB without radiographic evidence of esophageal dilatation and with no response to medication.…”
Section: Discussionmentioning
confidence: 97%
“…Two patients were reported by Alamoudi 10 one with AP and the other case of pneumonia due to migration of a connecting catheter. A case of thoracic empyema was reported by Krassas et al 11 A case of recurrent AP after LAGB was reported by Hofer et al 12 Zimlichman et al 13 reported a case of lung abscess. Nemni 14 reported a case of severe chronic cough after LAGB without radiographic evidence of esophageal dilatation and with no response to medication.…”
Section: Discussionmentioning
confidence: 97%
“…Neither study directly addressed the subject of post-operative pulmonary complications. Previous case series have tried to explain the association of LAGB with post-operative respiratory complications such as chronic cough [17,18], aspiration pneumonia [8,9,19], lung abscess [20,21], empyema [22], and bronchiectasis [10]. The leading hypotheses maintain that post-operative esophageal dilatation and dysmotility are responsible for both symptomatic and asymptomatic recurrent micro-aspirations of gastric secretions and contents, thereby causing inflammatory responses in the bronchial tree and lungs [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported long-term pulmonary complications following LAGB, the most common of which are aspiration pneumonia, lung abscess, and empyema. [ 5 6 ] In most cases, the complications following LABG manifest 6 months to 3 years after gastric banding. [ 4 5 7 ] Interestingly, our patient developed organizing pneumonia 12 years after LAGB, experiencing nocturnal GERD due to a tight gastric band.…”
Section: Discussionmentioning
confidence: 99%
“…Previously examined patients with LABG-related aspiration pneumonia also reported GERD symptoms. [ 4 5 6 7 ] However, aspiration pneumonia rarely can be diagnosed in the absence of significant symptoms and when it is due to occult aspiration. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%